Statistical Optimization of Conditions for Decolorization of Synthetic Dyes by Cordyceps militaris MTCC 3936 Using RSM. (4th February 2015) - Kaur, Baljinder; Kumar, Balvir; Garg, Neena; Kaur, Navneet
Abstract : In the present study, the biobleaching potential of white rot fungus Cordyceps militaris MTCC3936 was investigated. For preliminary screening, decolorization properties of C. militaris were comparatively studied using whole cells in agar-based and liquid culture systems. Preliminary investigation in liquid culture systems revealed 100% decolorization achieved within 3 days of incubation for reactive yellow 18, 6 days for reactive red 31, 7 days for reactive black 8, and 11 days for reactive green 19 and reactive red 74. RSM was further used to study the effect of three independent variables such as pH, incubation time, and concentration of dye on decolorization properties of cell free supernatant of C. militaris . RSM based statistical analysis revealed that dye decolorization by cell free supernatants of C. militaris is more efficient than whole cell based system. The optimized conditions for decolorization of synthetic dyes were identified as dye concentration of 300 ppm, incubation time of 48 h, and optimal pH value as 5.5, except for reactive red 31 (for which the model was nonsignificant). The maximum dye decolorizations achieved under optimized conditions for reactive yellow 18, reactive green 19, reactive red 74, and reactive black 8 were 73.07, 65.36, 55.37, and 68.59%, respectively.